Integration of planetary health in undergraduate and postgraduate medical education: protocol for a scoping review - Lindsey Sikora; Daniel I McIsaac; Husein Moloo; Rajajee Selvam; Nieve Seguin; Lisa Zhang; Ariane Lacaille-Ranger (BMJ Open, 2022)
Introduction Despite climate change being recognised as the greatest health threat of the 21st century, current medical education curricula do not reflect the urgency of the climate crisis. Preparing for climate-related health repercussions requires educational institutions to disseminate planetary health knowledge in a systematic way. We sought to evaluate the extent of the literature on the inclusion of planetary health in undergraduate and postgraduate medical education to guide curricular development.Methods and analysis A scoping review is being undertaken with a search strategy developed with a health sciences librarian. The search strategy was run on the following databases from inception to 22 June 2021: Medline, Embase, APA PsycINFO, CINAHL, Global Health, Scopus. This scoping review is being conducted as per methodology that has been previously outlined. Studies that discuss the implementation of planetary health education within undergraduate and postgraduate medical education will be included, whether they discuss formal inclusion or supplemental courses. To supplement our database search, data from the Health and Environment Adaptive Task Force’s National Report on Planetary Health Education, the Planetary Health Report Card and the Association for Medical Education in Europe Consensus Statement on Planetary Health and Education for Sustainable Healthcare will be included. As we anticipate varying methodologies, the data analysis will consist of both a quantitative and a qualitative component. Outcomes will be categorised within the domains of the Planetary Health Education Framework, which incorporates concepts of systems thinking, social justice and interconnection within nature as they apply to education for planetary health.Ethics and dissemination As no intervention or patient recruitment will be required, research ethics board approval is not applicable. We plan to disseminate our results via publication in a peer-reviewed journal or conference presentation.Trial registration number This protocol has been registered in Open Science Framework (10.17605/OSF.IO/7M6GZ).